MARKETING DALAM SEKTOR PUBLIK - Arifiani Widjayanti, (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
In the past, public sector was managed for the public issues, and private sector was focused on profit maximization. In recent times, both private and public sectors have to satisfy their stakeholders. For this purpose, marketing should be deeplyconsidered to be applied in the public sector. In public services, it will be suitable to change the word of 'consumer' to 'stakeholder' that is more common in the area of marketing. The target audience doesn't mean 'consumers' in real, but citizens. There are so many marketing management tools applicable for the context of public sector, such as 7Ps for marketing mix, project marketing, and customer satisfaction measured (stakeholder satisfaction measured). How marketing could beapplied in public sector becomes the homework of public leaders and government employeess. They should, in the first place, be able to identify which types of marketing are suitable for public services.